Pengaruh Trust, Perceived Value, dan E-WOM terhadap Keputusan Pembelian pada TikTok Live Commerce di Kalangan Gen Z - Dini Septi Aulina; Corry Yohana; Kusworo Kusworo (Indo Publishing, 2026)
This study aims to analyze the effect of trust, perceived value, and electronic word of mouth (E-WOM) on purchasing decisions among Generation Z consumers on TikTok Live Commerce. A quantitative approach with a causal cross-sectional design was employed, involving 140 respondents selected using purposive sampling in DKI Jakarta. Data were collected through online questionnaires and analyzed using IBM SPSS 31, including validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing. The findings indicate that perceived value and E-WOM have a positive and significant effect on purchasing decisions, both partially and simultaneously, while trust does not have a significant effect. E-WOM was identified as the most dominant variable influencing purchasing decisions. The coefficient of determination (R²) showed that the three independent variables jointly explained 68.1% of the variation in purchasing decisions, while the remaining 31.9% were explained by other factors outside the model. These findings support the perspective that consumer decisions in social commerce are not solely determined by trust, but are more strongly driven by perceived value and real-time electronic word of mouth, particularly through live comments and interactions during TikTok Live sessions. This study contributes to the understanding of consumer behavior in the context of social commerce and provides practical insights for businesses in managing live streaming strategies to enhance consumer purchasing decisions